Nurses' perceptions on barriers for implementing pressure ulcers preventive measures among critically ill patients at a tertiary teaching hospital, Tanzania - Dickson Ally Mkoka; Richard Andwilile (Elsevier, 2024)
Objectives: To explore nurse's perceptions on barriers for Implementing Pressure Ulcers Preventive Measures among critically ill patients. Research Design: An exploratory qualitative study design was employed. In-depth interviews were conducted with 15 nurses to explore their perceptions on barriers for preventing pressure ulcers among critically ill patient. Qualitative thematic analysis approach was used to analyze data. Study settings: Medical high dependent unit, surgical high dependent unit, medical Intensive Care unit and surgical intensive care units at tertiary teaching hospital. Findings: Seven themes emerged that describes nurses' perceptions on barriers for implementing pressure ulcers preventive measures among patients with critical illness. The themes are: Restrictions from therapeutic interventions and severity of patient condition; Shortage of staff and equipment for pressure ulcer prevention; Unbalanced shift staffing and competing need for patient care; health care providers' incompetence and carelessness; Lack of guidelines on implementing best practice for pressure ulcer prevention; Lack of accountability measures for negligence; and Minimal management's commitment for PUs prevention. Conclusion: This study reveals contextual based barriers for effective prevention of ppressure ulcers among critically ill patients. Nurses should be continuously empowered with competence for pressure ulcers prevention. This should go along with staffing and equipping critical care settings for pressure ulcers prevention. Managerial oversight is required for effective implementation of pressure ulcer preventive measures. This should include development of guidelines and policies, establishing accountability measures for negligence, malpractice as well as initiating clinical audit for reflective learning purpose.